Optimized dendritic cell vaccination induces potent CD8 T cell responses and anti-tumor effects in transgenic mouse melanoma models - Grees, Mareike; Baumann, Daniel; Eichmüller, Stefan B.; Offringa, Rienk; Utikal, Jochen; Umansky, Viktor (OncoImmunology, 2018)
Despite melanoma immunogenicity and remarkable therapeutic effects of negative immune checkpoint inhibitors, a significant fraction of patients does not respond to current treatments. This could be due to limitations in tumor immunogenicity and profound immunosuppression in the melanoma microenvironment. Moreover, insufficient tumor antigen processing and presentation by dendritic cells (DC) may hamper the development of tumor-specific T cells. Using two genetically engineered mouse melanoma models (RET and BRAFV600E transgenic mice), in which checkpoint inhibitor therapy alone is not efficacious, we performed proof-of-concept studies with an improved, multivalent DC vaccination strategy based on our recently developed genetic mRNA cancer vaccines. The in vivo expression of multiple chimeric MHC class I receptors allows a simultaneous presentation of several melanoma-associated shared antigens tyrosinase related protein (TRP)-1, tyrosinase, human glycoprotein 100 and TRP-2. The DC vaccine induced a significantly improved survival in both transgenic mouse models. Vaccinated melanoma-bearing mice displayed an increased CD8 T cell reactivity indicated by a higher IFN-γ production and an upregulation of activation marker expression along with an attenuated immunosuppressive pattern of myeloid-derived suppressor cells (MDSC) and regulatory T cells (Treg). The combination of DC vaccination with ultra-low doses of paclitaxel or anti-PD-1 antibodies resulted in further prolongation of mouse survival associated with a stronger reduction of MDSC and Treg immunosuppressive phenotype. Our data suggest that an improved multivalent DC vaccine based on shared tumor antigens induces potent anti-tumor effects and could be combined with checkpoint inhibitors or targeting immunosuppressive cells to further improve their therapeutic efficiency.
Gesehen am 15.05.2019